2013
DOI: 10.1038/srep02518
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic-like dynamics of amorphous drugs in the THz regime

Abstract: The high frequency dynamics of Indomethacin and Celecoxib glasses has been investigated by inelastic x-ray scattering, accessing a momentum-energy region still unexplored in amorphous pharmaceuticals. We find evidence of phonon-like acoustic dynamics, and determine the THz behavior of sound velocity and acoustic attenuation. Connections with ordinary sound propagation are discussed, along with the relation between fast and slow degrees of freedom as represented by non-ergodicity factor and kinetic fragility, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 48 publications
5
24
0
Order By: Relevance
“…The acoustic excitation ceases to be welldefined when the broadening is on the order of the frequency * aminnich@caltech.edu of the excitation, typically around a few THz. These general trends have been reported in a variety of glasses including polymers [18,28,30], metallic glasses [21], and monatomic glasses such as selenium [20], and others [17,19,22,27,29].…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…The acoustic excitation ceases to be welldefined when the broadening is on the order of the frequency * aminnich@caltech.edu of the excitation, typically around a few THz. These general trends have been reported in a variety of glasses including polymers [18,28,30], metallic glasses [21], and monatomic glasses such as selenium [20], and others [17,19,22,27,29].…”
Section: Introductionsupporting
confidence: 52%
“…The broadening of the inelastic peaks, (q), of a-Si at 300 K versus wave vector are shown in Fig. 7(a) along with those of various types of amorphous materials from metallic glasses to polymers studied by IXS [18,21,27,30] and the computational work of Ref. [42].…”
Section: B Ixs Measurement Comparison Among Several Amorphous Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A numerical simulation study [33] predicted that the origin of the boson peak is the Ioffe-Regal limit for a transverse acoustic mode, and its frequency is proportional to the shear modulus l. On the other hand, a study of the glassy IMC by the inelastic X-ray scattering [37] reported that the Ioffe-Regal limit for the longitudinal acoustic mode is about 0.6 THz. That frequency of the IMC is slightly higher than the m BP-Raman which is related to the transverse acoustic mode.…”
Section: Resultsmentioning
confidence: 96%
“…According to Dalal et al 29 , the difference in density between the 2 samples should be around 0.3%. Besides, stable glasses embedded with higher density also exhibit higher values of the sound velocity up to 10% [30][31][32] , therefore it is reasonable to expect that more stable glasses will also exhibit an enhancement of the thermal conductivity.…”
Section: Real-time Measurement Of Thin-film Growth: Sensor Proof Of Cmentioning
confidence: 99%